Comparative Analysis of Systematic, Scoping, Umbrella, and Narrative Reviews in Clinical Research: Critical Considerations and Future Directions - Mohamad Motevalli (International Journal of Clinical Practice)
Review studies play a key role in the development of clinical practice by synthesizing data and drawing conclusions from multiple scientific sources. In recent decades, there has been a significant increase in the number of review studies conducted and published by researchers. In clinical research, different types of review studies (systematic, scoping, umbrella, and narrative reviews) are conducted with different objectives and methodologies. Despite the abundance of guidelines for conducting review studies, researchers often face challenges in selecting the most appropriate review method, mainly due to their overlapping characteristics, including the complexity of matching review types to specific research questions. The aim of this article is to compare the main features of systematic, scoping, umbrella, and narrative reviews in clinical research and to address key considerations for selecting the most appropriate review approach. It also discusses future opportunities for updating their strategies based on emerging trends in clinical research. Understanding the differences between review approaches will help researchers, practitioners, journalists, and policymakers to effectively navigate the complex and evolving field of scientific research, leading to informed decisions that ultimately enhance the overall quality of healthcare practices.